2009
DOI: 10.1063/1.3075763
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium oxide nanowire phase and orientation analyzed by Raman spectroscopy

Abstract: Phase-selective growth of VO2 and V2O5 nanowires was realized via catalyst-free physical vapor deposition from bulk VO2 powder. Single nanowire Raman spectroscopy was used to analyze the distribution of the vanadium oxide phases within the reactor. VO2 (V2O5) nanowires were identified by characteristic peaks at 197, 224, and 620 cm−1 (149, 700, and 994 cm−1). Electron diffraction and polarization-dependent Raman spectra indicated that the growth directions of VO2 and V2O5 nanowires were [100] and [010]. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 26 publications
12
39
0
Order By: Relevance
“…As shown in Fig. 1(c), peaks in the Raman spectra were assigned to VO 2 (M) (denoted by triangles), in good agreement with previous studies, [21][22][23] and no peak from any secondary phase was observed for any of the films. This is consistent with the results of the XRD measurements.…”
Section: A Crystal Structures and Phase Diagramsupporting
confidence: 75%
“…As shown in Fig. 1(c), peaks in the Raman spectra were assigned to VO 2 (M) (denoted by triangles), in good agreement with previous studies, [21][22][23] and no peak from any secondary phase was observed for any of the films. This is consistent with the results of the XRD measurements.…”
Section: A Crystal Structures and Phase Diagramsupporting
confidence: 75%
“…This is likely due to the nanosize of the wire whose effect would be greatest when exciting modes in its short direction. 15,16 One notes in passing that although the Raman intensity of the B 2g band is weak so that the detailed polarization angle dependence of its intensity is not as reliable as that for the E g mode, its lack of polarization angle dependences is what is expected for a RuO 2 NW grown along the ͑001͒ direction.…”
Section: -4mentioning
confidence: 99%
“…[7][8][9][10][11] Polarized Raman measurements have also been carried out on single NWs unambiguously identifying the NW's growth direction and comparing the results with those obtained using electron diffraction. [12][13][14][15][16] As with electron microscopy, Raman spectroscopy can be used as a real-time probe under a broad range of experimental conditions. In this letter, we report the use of polarized Raman scattering as a rapid and reliable method for determining the growth direction of a single RuO 2 NW.…”
Section: -4mentioning
confidence: 99%
“…These are the fundamental bases for creating and tuning the novel material properties that have extensively applied in sensors, indicators, bio-imaging detection, optical devices, data security, missile plume detection and defence applications [33][34][35][36][37][38][39][40][41][42] . The remarkable physicochemical characteristics of these MON can be attributed to their miniaturised size (surface area, size distribution), chemical composition (crystallinity, purity), surface structure (surface-reactivity, sensitivity, and groups), porosity, shape, aggregation and defect centers (charged and neutral vacancies, F + or F 2+ and F 0 , respectively).…”
Section: Introductionmentioning
confidence: 99%